Ajaran dalam Teks Śilakramaning Aguron-Guron - Ida Bagus Subrahmaniam Saitya; Nyoman Gede Wirawan; G. Arya Anggriawan (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
The problem of juvenile delinquency has special attention from various parties and other relevant agencies. But some parties consider that is not something extraordinary. The naughtiness is considered as a psychological phase that is natural and everyone will experience at a certain age. Teen ages are considered as the puberty phase where they are looking for self-identity. When looking for that identity, teenagers or students are often misdirected or misguided. In a traditional doctrine contained in the Lontar Śilakramaning Aguron-guron which is one of the sources literature used as a rule of study. This article aims to explore, elevate, and introduce sources of local wisdom as a source of information to increasing the knowledge. The meaning of the Lontar Śilakramaning Aguron-guron text as one of the guidelines for realizing students who have high character, including students are obliged to dutiful and obedient to teachers; students are able to uphold the principles of truth; students are able to distance themselves from inappropriate characters, attitudes, and behaviors; students must use a polite, clean, and neat clothing; students are required to have pure hearts and minds; students are able to control the passions.